SUCCESSION IN THE EDUCATIONAL PROCESSA CHIEVING HIGH EFFICIENCY AND QUALITYFUTURE ECONOMIC SECTOR SPECIALISTS - Теловата, М. Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
Analyzing thoughts of predecessors, and also results of own work, the author sees the decision of a problematic of continuity: should be generated uniform the information-methodical environment of continuity, it agree which using toolkit the concept of formation and concrete educational processes should be built